Semana cultural en la Universidad Estatal a Distancia. (UNED, 2023)
Equipo femenino de funcionarias Wendy Pinnock Pinnock, Dayana Valverde Valverde Baltodano, Carolina Sanchez Cabezas, Liliana Picado Alvarado, Yinnia Mora Ordonez, Kattya Torres Chinchilla